Renal Protective Effects of L-Carnitine on Lead-Induced Nephropathy in Wistar Rats - Hejazy, Marzie; Najafi, Davood (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: Lead is a heavy metal used in industries in developing countries. Lead exposure remains a widespread problem. Lead may induce molecular damage in the kidney as a consequence of Reactive Oxygen Species (ROS) formation, induction of caspase-3, and apoptosis. Methods: Thirty male Wistar rats (Mean±SD weight: 300±20 g) were randomly divided into 3 equal groups: control (normal saline, oral), lead group (lead 100 mg/kg/d, oral) and lead+L-Carnitine (lead 100 mg/kg+L-Carnitine 200 mg/kg, intraperitoneal injection) for one week. At the end of the experiment, plasma creatine kinase activity, plasma creatinine and urea concentrations and plasma Superoxide Dismutase (SOD), Glutathione Peroxidase (GPx), catalase and nitric oxide levels were determined. Glutathione and malondialdehyde levels in renal tissue were also measured. Results: Creatine kinase, creatinine and urea levels increased significantly, in the group treated with lead (P<0.05), compared to the control group. Administration of L-Carnitine in (Lead+carnitine treated group) significantly (P<0.05) decreased creatine kinase activity and plasma urea and creatinine contents. Enzymatic activity (SOD, GPx, and CAT) decreased significantly in the lead group, in comparison with the control group (P<0.05). Treatment with L-Carnitine significantly retrieved the depletion in enzyme activity (P<0.05). However, there were no significant differences in the GPx parameter between the Lead+carnitine group, in comparison with the control group. Conclusion: L-Carnitine administration in rats with lead-induced nephropathy led to improved kidney protection, due to the reduction of Lipid Peroxidation (LPO). Furthermore, L-Carnitine prevents the adverse effects of Reactive Oxygen Species (ROS), which is an important biomolecules mechanism.